LEARNING ORGANISATION: UTOPIA OR PRACTICAL? - Adiningrum, Tatum Syarifah (Journal of Business Strategy and Execution, 2012)
Organisational learning and learning organizational concept are not new in management discipline, however the high popularity of these construct is growing in 1990s onwards to both academics and business managers. From organisational perspective, in order to keep its competitive advantage, to be successful continually, organisations have to keep improving its products and service, and to be able to do that, organisations have to learn, thus becoming a learning organisation. Definitions of learning organisation are varied from each author, from a simple, idealistic to a highly practical one. To manage organisational learning, there are also different ranges of discussions from different academics, ranging from the vague and utopian to highly practical approach. Although engaging in organisational learning is very useful for the development of organisations, becoming a learning organisation is not the one and truly aswer to the sustainability of an organisation. Organisation should pursue change to a better performance, but not all organisation have to change with the same pace and intencity. The most reasonable thing to do in addapting the learningÂ  organisation notion is to consider the sensitiveness of culture and needs, and to decide to what degree an organisation would like to adapt it.